Neural Regulation of Cancer: Cancer‐Induced Remodeling of the Central Nervous System. Issue 9 (8th July 2022) - Krishna, Saritha; Hervey‐Jumper, Shawn L.
Abstract: In recent years, there have been significant advances in understanding the neuronal influence on the biology of solid tumors such as prostate, pancreatic, gastric, and brain cancers. An increasing amount of experimental evidence across multiple tumor types strongly suggests the existence of bidirectional crosstalk between cancer cells and the neural microenvironment. However, unlike cancers affecting many solid organs, brain tumors, namely gliomas, can synaptically integrate into neural circuits and thus can exert a greater potential to induce dynamic remodeling of functional circuits resulting in long‐lasting behavioral changes. The first part of the review describes dynamic changes in language, sensory, and motor networks following glioma development and presents evidence focused on how different patterns of glioma‐induced cortical reorganization may predict the degree and time course of functional recovery in brain tumor patients. The second part focuses on the network and cellular‐level mechanisms underlying glioma‐induced cerebral reorganization. Finally, oncological and clinical factors influencing glioma‐induced network remodeling in glioma patients are reviewed. Abstract : Brain tumors, namely gliomas, can synaptically integrate into neural circuits and thus exert a greater potential to induce dynamic remodeling of functional circuits resulting in long‐lasting behavioral changes. Glioma‐induced cerebral reorganization entails both network and cellular‐level mechanisms and induces dynamic changes in language, sensory, and motor networks.